To the question about the rules of working design in land management - Martyn, A.; Kolhanova, І. (Land Management, Cadastre and Land Monitoring, 2021)
Proposed scientific and methodological approaches to the development of working projects of land management regarding the implementation of measures for land reclamation, removal and transfer of the fertile soil layer, conservation of degraded and unproductive lands, improvement of agricultural and forestry lands, protection of lands from erosion, flooding, waterlogging, secondary salinization, desiccation, landslides, compaction, acidification, pollution by industrial and other wastes, radioactive and chemical substances, the structure and content of such projects has been developed. A complex of qualitative and quantitative indicators, parameters, regulating the development of working projects of land management, taking into account environmental, economic, social, natural-climatic and other conditions is proposed.Keywords: recultivation of disturbed lands, land tenure, detailed design of land management, soil cover, fertile soil layer.